Improved interfacial properties of carbon fiber composites by building stress transition layer with carbon nanotubes. Issue 7 (18th December 2017) - Zhang, Wenqing; Yang, Qing; Deng, Xi; Bai, Gang; Xiao, Wei; Sui, Gang; Yang, Xiaoping
Abstract: For the purpose of improvement in interfacial property of carbon fiber composites through a facile process, the carboxyl‐functionalized multiwalled carbon nanotubes (MWCNTs‐COOH) were incorporated into the surface of JH‐T800 carbon fiber using sizing and deposition technology. The surface morphology of MWCNTs‐COOH‐modified carbon fibers and fracture surfaces of unidirectional carbon fiber composites were observed via scanning electron microscopy and atomic force microscopy. According to the results of composites fragmentation test, the adoption of MWCNTs‐COOH‐modified carbon fibers resulted in the improved carbon fiber/epoxy matrix interfacial bonding and interlaminer property by 32.1% and 31.9%, respectively. Through the combination of the above two kinds of pretreating process of carbon fibers, a stress transition layer with the gradient distribution of MWCNTs was built between carbon fiber and resin matrix, which was favorable for releasing stress concentration and hindering the propagation of crack, resulting in a higher reinforcing efficiency for the existing carbon fiber composites.